The moderating effect of social cognitive factors on self-management activities and HbA1c in Thai adults with type-2 diabetes - Somsak Thojampa; Barbara Mawn (Elsevier, 2017)
Background: Diabetes mellitus (DM) has become a serious chronic disease. Self-management strategies help persons with DM make choices which will develop skills needed to reach their goal of blood glucose control and allow them to be successful in reaching goals. Objective: To examine the impact of self-management activities on HbA1c for persons with DM and to examine the impact of social support, self-efficacy and Buddhist values as moderators on the relationship between the self-management activities and HbA1c. Method: This study is a cross-sectional design. The sample included 401 Thai adults diagnosed with type 2 diabetes, aged 20-65 years old who had at least one HbA1c test in the last three months were recruited. Participants completed four questionnaires to measure self-management activities, as well as self-efficacy, Buddhist values and social support as moderating factors on self-management activities and HbA1c. Results: The self-management activities were negatively associated (β = −2.05, p ≤ 0.001) with HbA1c. The Social support, self-efficacy and Buddhist values had a significant interaction effect between selfmanagement activities and HbA1c (β = −0.97, p ≤ 0.05, β = −0.18, p ≤ 0.05 and β = −2.76, p ≤ 0.001). Conclusion: The diabetes self-management activities were more strongly associated with HbA1c under conditions of high social support, self-efficacy and health beliefs with Buddhist values. Future interventions for T2DM self-management programs should incorporate mechanisms to measure and support these factors. Keywords: Self-management activities, Social support, Self-efficacy, Buddhist values, Type-2 diabetes mellitus